The resonant interaction between anions or vacancies in ZnON semiconductors and their effects on thin film device properties - Jozeph Park (Nature Portfolio, 2017)
Abstract Zinc oxynitride (ZnON) semiconductors are suitable for high performance thin-film transistors (TFTs) with excellent device stability under negative bias illumination stress (NBIS). The present work provides a first approach on the optimization of electrical performance and stability of the TFTs via studying the resonant interaction between anions or vacancies in ZnON. It is found that the incorporation of nitrogen increases the concentration of nitrogen vacancies (VN +s), which generate larger concentrations of free electrons with increased mobility. However, a critical amount of nitrogen exists, above which electrically inactive divacancy (VN-VN)0 forms, thus reducing the number of carriers and their mobility. The presence of nitrogen anions also reduces the relative content of oxygen anions, therefore diminishing the probability of forming O-O dimers (peroxides). The latter is well known to accelerate device degradation under NBIS. Calculations indicate that a balance between device performance and NBIS stability may be achieved by optimizing the nitrogen to oxygen anion ratio. Experimental results confirm that the degradation of the TFTs with respect to NBIS becomes less severe as the nitrogen content in the film increases, while the device performance reaches an intermediate peak, with field effect mobility exceeding 50 cm2/Vs.